Development of ko-standardization method for reactor neutron activation analysis - Ibrahim Abugassa,; Sukiman Sarmani ,; Supian Samat, (Universiti Kebangsaan Malaysia, 1996)
Two important parameters for utilizing Ko-standardization method namely, absolute peak efficiency at reference position and peak-to-total ratio at different geometrical positions using standard point sources and HPGe were experimentally determined. Coincidence correction factor, C, for reference position and certain nuclides were also calculated and all almost equal to one. The importance and implication of this work to the K0-standardization method are presented. Other essential nuclear parameters which have to be experimentally determined or obtained from literature are also presented.